Radiografi sebagai alat penunjang diagnosa dan kontrol persembuhan laminitis pada kuda - Budhy Jasa Widyananta; Fitri Dewi Fathiyah; Wakhid Nur Hidayat (ARSHI Veterinary Letters, 2018)
Laminitis is an inflammation of hoof lamina which support the pedal bone to stay to it normal position. One crossbreed horse was found severely lame and lying down most of the time. Lameness examination was showing bilateral lameness of his fore hooves. Both are pain on the hoof test and digital pulse was positive. First X-ray were taken and show rotation and abnormal tip of the pedal bone, where the left fore was worse. Hoof trimming, corrective shoeing, sistemic and oral anti-inflammatory, cold compress, feeding program were combined for the treatment. Three months later, the horse was reexamined and x ray was taken. Another trimming and shoeing were followed with series of x ray shown good result. There are many different method have been suggested to provide support for an unstable pedal bone. Hoof wall resection and corrective sole on the heel area for corrective shoeing. Horse was trotted sound and starts his lower level of work few months after. X ray may identify the rotation angle of pedal bone and their effect to the bone also guide the treatment of laminitis.